THE VARIOUS USES OF WHEY PROTEIN IN PHYSICAL ACTIVITY PRACTITIONERS (CIPEEX, 2022)
THE OBJECTIVE OF THIS RESEARCH WAS TO IDENTIFY THE VARIOUS FUNCTIONS OF THE USE OF MILK PROTEIN (WHEY PRONTEIN) FOR THE RESULTS OF PHYSICAL ACTIVITY PRACTITIONERS. FOR THIS, BIBLIOGRAPHIC RESEARCH WAS CARRIED OUT IN THE SCIELO AND PUMED DATABASES, USING THE KEYWORDS WHEY PROTEIN, PHYSICAL ACTIVITY, MUSCLE MASS GAIN AND PHYSICAL RECOVERY. ONLY ORIGINAL ARTICLES PUBLISHED BETWEEN 2012 AND 2022 WERE SELECTED. THE RESULTS SHOWED SEVERAL SITUATIONS, INCLUDING BENEFITS IN STRENGTH AND MUSCLE MASS, WHEN COMBINED WITH VITAMIN D, IN MEN WHO PRACTICE RESISTANCE TRAINING. EVEN WITHOUT VITAMIN D COMBINATION, WHEY PROTEIN SUPPLEMENTATION ALSO SHOWED RESULTS IN PROMOTING INCREASED MUSCLE STRENGTH AND FUNCTIONAL CAPACITY IN PRECONDITIONED ELDERLY WOMEN AND IN YOUNG ADULTS AND MIDDLE-AGED WOMEN. PREVENTION OF SARCOPENIA HAS ALSO BEEN OBSERVED IN OLDER WOMEN. IT WAS OBSERVED THAT THERE ARE BENEFITS THAT GO BEYOND THE GAIN OF LEAN MASS, BUT THE DOSES THAT GENERATE RESPONSES AND RESULTS VARY ACCORDING TO THE PUBLIC.
Keywords: whey protein; physical activity; muscle mass gain; physical recovery